Coastal Marine Geochemical Provinces and Background Values in Sediments: A Methodological Approach - Romano, Elena; Ausili, Antonella; Bergamin, Luisa (Frontiers in Marine Science, 2022)
The Italian approach to determining background values (BGVs) of metals and trace elements in marine sediments according to the national legislation transposing the water framework directive (WFD) has been illustrated. This study may be helpful for all countries that need to establish local BGVs for the correct assessment of contamination in areas with wide geological and geochemical variability and, particularly, for those that need assessing the good chemical status according to the WFD. The first step was clearly defining the BGV as a concentration value that allows for discriminating between natural and anthropogenic contributions and establishing the concept of the marine geochemical province (MGP). Successively, criteria for delimiting the MGPs were provided, similar to those adopted for the geochemical mapping of the territory. Finally, an integrated method based on the constitution of a dataset from unpolluted sediments obtained from pre-industrial levels was chosen for determining the BGV.